Impact of hyperkalaemia definition on incidence assessment: implications for epidemiological research based on a large cohort study in newly diagnosed heart failure patients in primary care. Issue 1 (December 2016) - Martín-Pérez, Mar; Ruigómez, Ana; Michel, Alexander; García Rodríguez, Luis
Abstract Background Various definitions of hyperkalaemia have been used in clinical research, and data from routine clinical practice on its incidence are sparse. We aimed to establish the incidence of hyperkalaemia in patients with newly diagnosed heart failure in the UK general population using different definitions for the condition. Methods We conducted a large retrospective cohort study using data from The Health Improvement Network primary care database. Patients with newly diagnosed heart failure (N = 19, 194) were identified and followed until the first occurrence of hyperkalaemia. Different serum potassium (K+ ) thresholds were evaluated as possible definitions for hyperkalaemia, and incidence rates (IRs) calculated using a final operational definition both overall and among patient sub-groups. Results IRs of hyperkalaemia ranged from 0.92–7.93 per 100 person-years according to the definition. Based on considerable differences in the serum K+ normal range used between practices, 2176 (11.3 %) individuals were identified with a record of hyperkalaemia using our operational definition of a proportional increase of ≥10 % above the upper bound of the normal range: IR 2.90 per 100 person-years (95 % CI 2.78–3.02) over a mean follow-up of 3.91 years. Incidence rates were higher in older patients, and in those with diabetes or renal impairment. Conclusions Hyperkalaemia is a common finding in heart failure patients in primary care, but its incidence can vary nearly ten-fold depending on its definition. Since assessment of hyperkalaemia risk is essential for therapeutic decision making in heart failure patients, this finding warrants consideration in future epidemiological studies.